A Broad-Range Disposable Electrochemical Biosensor Based on Screen-Printed Carbon Electrodes for Detection of Human Noroviruses - Wang, Nan; Pan, Guiying; Guan, Shimin; Rong, Shaofeng; Wang, Dapeng; Gao, Zhiyong; Tian, Peng; Li, Qianqian (Frontiers in Bioengineering and Biotechnology, 2022)
Human noroviruses (HuNoVs) are the major non-bacterial pathogen causing acute gastroenteritis in people of all ages worldwide. No stable culture system in vitro is available for routing detection of multiple strains of HuNoV. A simple and rapid method for detection of HuNoVs is of great significance for preventing and controlling this pathogen. In this work, an electrochemical biosensor for sensitive and fast detection of HuNoVs was constructed based on screen-printed carbon electrode (SPCE). Gold nanoparticles and protein-A were applied on SPCE surface for enhancement of the electrical signals and the linkage of antibodies with a fixed orientation, respectively. A monoclonal antibody (MAb) against S domain protein of viral capsid (VP1) was further immobilized on SPCE to bind HuNoV specifically. Binding of VP1 to the coated MAbs resulted in a reduction of conductivity (current) measured by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The reduction in the current was correlated to the concentration of VP1/HuNoVs. The detection limitation of Genogroup I.1 (GI.1) VP1 and Genogroup II.4 (GII.4) VP1 was 0.22 ng/mL and 0.37ng/mL, respectively. The detection limitation of both GI and GII HuNoVs in clinical fecal samples was 104 genomic copies/mL. The results could be obtained in 1 hour. We demonstrated that this disposable electrochemical biosensor was a good candidate for rapid detection of different genogroups and genotypes HuNoVs.